Fostering Undergraduate Data Science - Yavuz, Fulya Gokalp; Ward, Mark Daniel (TAYLOR & FRANCIS INC, 2020)
Data Science is one of the newest interdisciplinary areas. It is transforming our lives unexpectedly fast. This transformation is also happening in our learning styles and practicing habits. We advocate an approach to data science training that uses several types of computational tools, including R, bash, awk, regular expressions, SQL, and XPath, often used in tandem. We discuss ways for undergraduate mentees to learn about data science topics, at an early point in their training. We give some intuition for researchers, professors, and practitioners about how to effectively embed real-life examples into data science learning environments. As a result, we have a unified program built on a foundation of team-oriented, data-driven projects.
Keywords: Computation; Learning; Mentoring; Statistical projects; Teamwork; Mathematics